1974
DOI: 10.1159/000123655
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Vigilance in Animal Life

Abstract: Vigilance is an important facet of animal life andparticularly so in relation to three areas: external danger, the exploitation of environmental resources, and intraspecific communication. The second of these involves, in addition to vigilance, an active search of the environment. The organization of the nervous system, however, imposes certain limitations on the effectiveness of vigilance and these are described, with particular reference to experimental studies of vigilance in man. Three types of strategy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 13 publications
0
37
0
2
Order By: Relevance
“…However, it has been associated with mechanisms such as habituation and neural inhibition (reviewed in Mackworth 1968Mackworth , 1969. Regardless of the exact proximate mechanisms, it is widely agreed that vigilance decrement during continuous activity, and vigilance recovery during rest and sleep, do occur (Dimond & Lazarus 1974;Jerison 1977 Parasuraman 1982;Horne 1988;Steriade et al 1993). Furthermore, probably everybody is familiar with the feeling of getting 'tired' or 'sleepy' while conducting some difficult activity, and then becoming 'refreshed' after rest or sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been associated with mechanisms such as habituation and neural inhibition (reviewed in Mackworth 1968Mackworth , 1969. Regardless of the exact proximate mechanisms, it is widely agreed that vigilance decrement during continuous activity, and vigilance recovery during rest and sleep, do occur (Dimond & Lazarus 1974;Jerison 1977 Parasuraman 1982;Horne 1988;Steriade et al 1993). Furthermore, probably everybody is familiar with the feeling of getting 'tired' or 'sleepy' while conducting some difficult activity, and then becoming 'refreshed' after rest or sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of non-human subjects have been restricted to neurobiological research (Foote et al 1980;Aston-Jones et al 1984). Nevertheless, the problem of sustained vigilance is highly relevant for the daily patterns and types of activity conducted by animals in their natural settings (Dimond & Lazarus 1974).…”
mentioning
confidence: 99%
“…In addition, there is also a potential trade-off between resting and vigilance (Ruckstuhl et al 2003). Vigilance is a behavior that increases the probability that an animal will detect a stimulus at a given time (Dimond & Lazarus 1974). When the stimulus occurs, musk deer cease resting and show standing-alert behavior to avoid predation or disturbance, while reducing time spent feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical discussion (Caraco, 1979a;Elgar & Catterall, 1981;Pulliam et al, 1982;Hart & Lendrem, 1984) and experimental studies (Dimond & Lazarus, 1974;Powell, 1974;Siegfried & Underhill, 1975, Caraco, 1979bBarnard, 1980;Barnard et al, 1982; and others) have suggested that an individual feeding in a flock can reduce its investment in surveillance for predators because it benefits from the surveillance of other members of the group. Hence, a bird joining a flock can devote more time to searching for food and feeding.…”
Section: Introductionmentioning
confidence: 99%